Biomechanical behavior of mandible with posterior marginal resection using finite element analysis. (8th November 2021) - Cheng, Kang‐jie; Liu, Yun‐feng; Wang, Russell; Yuan, Zi‐xi; Jiang, Xian‐feng; Dong, Xing‐tao
Abstract: This study aims to characterize biomechanical behavior of various designs of posterior mandibular marginal resection under functional loadings using finite element method. The ultimate goal of this work is to provide clinically relevant information to prevent postoperative fracture and to stipulate prophylactic internal fixation for planning of marginal mandibulectomy. A 3D mandibular master model was reconstructed from cone beam computed tomography images. Different marginal resection models were created based on three design parameters, namely, defect curvilinear radius, anterior–posterior defect width and residual height of the mandibular body. Functional loadings from incisors (60 N) and contralateral first molar area (200 N) were applied to designed models and stress patterns were compared of five groups with curvilinear radius from 0 (conventional rectangular shape), 2.5, 3.5, 5, and 6 mm. Models with 25, 35 and 45 mm defect width mimic defects varied from canine to 3rd molar were tested. Residual height range from 10 to 4 mm was assessed. The results show high stresses predominated in the occlusal area and the posterior inferior border near the resection corner. The average maximum stress decreased by 29.8% ( r = 2.5 mm), 51.9% ( r = 3.5 mm), 54.4% ( r = 5 mm), and 59.3% ( r = 6 mm) compared to the baseline of r = 0 mm. The results from the combined defect width/residual height models demonstrate the increase of defect width and the decrease in residual height resulted in the increase of maximum stress. Our data also confirm that the factor of residual height supersedes defect width in terms of prevention of postoperative fracture when considering resection design. Abstract : With various curvilinear radius design, 3.5 mm showed the best stress distribution during functional loadings. The combined defect width/residual height models demonstrated the increase of defect width and the decrease in residual height resulted in the increase of maximum stress. Residual height supersedes defect width in terms of prevention of postoperative fracture when considering resection design.